PENGARUH LEVERAGE TERHADAP MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016 - Tanti Dahlianti Nazilah, 14.05.52.0027; Kartika, Andi (Students' Journal of Accounting and Banking, 2018)
This study aims to determine and test the effect of leverage on earnings management with good corporate governance as a moderation variable.This study used a sample of 195 manufacturing companies listed on the Indonesia Stock Exchange for the period of 2013-2016. The sample was obtained by purposive sampling. The type of data used is secondary data. Research data were analyzed by analysis of Moderated Regression Analysis (MRA). The results showed that leverage has a significant positive effect on earnings management. Managerial ownership is unable to moderate the effect of leverage on earnings management. Institutional ownership can weaken the effect of leverage on earnings management. And independent board of commissioners are able to strengthen the leverage effect on earnings management. Keywords: leverage, earnings management, managerial ownership, institutional ownership and independent board of commissioners